2019
DOI: 10.1021/acs.jpcb.9b04027
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Nuclear Reorganization and Interplay of Bright and Dark Excited States

Abstract: We report quantum chemical calculations using multireference perturbation theory (MRPT) with the density matrix renormalization group (DMRG) plus photothermal deflection spectroscopy measurements to investigate the manifold of carotenoid excited states and establish their energies relative to the bright state (S 2 ) as a function of nuclear reorganization. We conclude that the primary photophysics and function of carotenoids are determined by interplay of only the bright (S 2 ) and lowest-energy dark (S 1 ) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 149 publications
5
67
0
2
Order By: Relevance
“…Carotenoids, instead, are good candidates for the quencher in virtue of their complex excited states photodynamics, which result in a ladder of intermediate short-lived states. [76][77][78] The perturbation of the local interaction with chlorophylls open up an energy transfer channel that ends with a fast internal conversion to the ground state. 15,16 To summarise, our data on major LHCII in monomeric form obtained from different xanthophyll mutants showed that the carotenoid chemical structure and properties do not hinder the capacity of the complexes to undergo dissipative conformational changes.…”
Section: Resultsmentioning
confidence: 99%
“…Carotenoids, instead, are good candidates for the quencher in virtue of their complex excited states photodynamics, which result in a ladder of intermediate short-lived states. [76][77][78] The perturbation of the local interaction with chlorophylls open up an energy transfer channel that ends with a fast internal conversion to the ground state. 15,16 To summarise, our data on major LHCII in monomeric form obtained from different xanthophyll mutants showed that the carotenoid chemical structure and properties do not hinder the capacity of the complexes to undergo dissipative conformational changes.…”
Section: Resultsmentioning
confidence: 99%
“…Early studies of excited states with DMRG were concerned with the dissociation curves of diatomic molecules, but genuine applications of photophysical and photochemical processes are slowly coming to light. Examples include the photochromic ring opening of spiropyran, the low‐energy spectrum of [2Fe‐2S] and [4Fe‐4S] clusters, the low‐lying singlet states of trans ‐polyenes up to C 20 H 22 , the electronic structure of a naphthalene excimer, singlet donor–acceptor copolymers for singlet fission applications, photocyclizations, the delayed fluorescence in carbene‐metal amides, and excitations in carotenoids …”
Section: The Challenges In Electronic Structure Theorymentioning
confidence: 99%
“…Examples include the photochromic ring opening of spiropyran, [52] the low-energy spectrum of [2Fe-2S] and [4Fe-4S] clusters, [53] the low-lying singlet states of trans-polyenes up to C 20 H 22 , [54] the electronic structure of an aphthalene excimer, [55] singlet donor-acceptor copolymers for singlet fission applications, [56] photocyclizations, [57] the delayed fluorescence in carbenemetal amides, [58] and excitations in carotenoids. [59] As DMRG allows inclusion of many orbitals,the question arises whether it is possible to devise an automated mechanism to identify the most important ones for as pecific problem. Thes election of the active space is usually done manually,w hich makes it tedious and possibly subjective.…”
Section: Minireviewsmentioning
confidence: 99%
“…Einige Beispiele sind die photochrome Ringçffnungsreaktion von Spiropyranen, [52] das niederenergetische Spektrum von [2Fe-2S]-und [4Fe-4S]-Clustern, [53] die niedrigliegenden Singulett-Zustände der trans-Polyene bis C 20 H 22 , [54] die Elektronenstruktur des Naphthalin-Excimers, [55] Singulett-Donor-Akzeptor-Copolymere fürS inglet-Fission-Anwendungen, [56] Photozyklisierungen, [57] die zeitverzçgerte Fluoreszenz in Carben-Metall-Amid-Verbindungen [58] und Anregungen in Carotenoiden. [59] Da DMRG eine große Anzahl an aktiven Orbitalen beschreiben kann, stellt sich die Frage,o be sm çglich ist, eine automatisierte Methode zur Bestimmung der wichtigsten aktiven Orbitale füre in gegebenes Problem zu finden. Normalerweise wird die Auswahl des aktiven Raumes manuell vorgenommen, was eine langwierige und subjektive Prozedur ist.…”
Section: Multi-konfigurations-und Multi-referenz-methodenunclassified
“…Ältere Untersuchungen angeregter Zustände mit DMRG behandelten die Dissoziationskurven von zweiatomigen Molekülen, aber die Anzahl aufwendigerer Studien von photophysikalischen und photochemischen Prozessen wächst stetig. Einige Beispiele sind die photochrome Ringöffnungsreaktion von Spiropyranen, das niederenergetische Spektrum von [2Fe‐2S]‐ und [4Fe‐4S]‐Clustern, die niedrigliegenden Singulett‐Zustände der trans ‐Polyene bis C 20 H 22 , die Elektronenstruktur des Naphthalin‐Excimers, Singulett‐Donor‐Akzeptor‐Copolymere für Singlet‐Fission‐Anwendungen, Photozyklisierungen, die zeitverzögerte Fluoreszenz in Carben‐Metall‐Amid‐Verbindungen und Anregungen in Carotenoiden …”
Section: Die Herausforderungen Der Elektronenstrukturunclassified